PARTICIPATION OF PARENTS IN PROMOTING EARLY CHILDHOOD DEVELOPMENT AT THE DEVELOPMENT CENTER PRESCHOOL CHILDREN, BANGKOK, LAK SI DISTRICT - Kettanom, Thasporn (Journal of MCU Nakhondhat, 2024)
The objective of this quantitative research was to study the level and compared parental participation in promoting early childhood development at the Bangkok Preschool Child Development Center, Lak Si District. The sample group used in the research was 152 parents of students in the Bangkok Preschool Child Development Center, Lak Si District. The research instrument was a questionnaire. It was characterized by a 5 - level rating scale. It was a consistency index ranging from 0.67 - 1.00 with a confidence value of 0.97. Statistics used in data analysis were percentages, means, standard deviations, T - test, One - way analysis of variance and pairwise testing with Scheffe’s method were used. The research results found that parental involvement in promoting early childhood development was at a high level. When considering each aspect, it was found to be at a high level in every aspect, arranged in order of averages values from highest to lowest as follows: Social, emotional, physical, and intellectual development. As for the results of comparing parents’ participation in promoting early childhood development, parents of different ages were involved. When considering each aspect, it was found that physical and intellectual development were significantly different at the .05 level and the social aspect with no difference. Parents with different levels of education were involved. Overall, result indicates that each aspect was significantly different at the .05 level. Parents from different occupations were involved. Parents with different incomes were involved. They were different overall and each aspect was different, statistically significant at the .05 level.